Evaluation of the Physical and Adhesive Properties of Natural Weathering Asphalt - Yanzhu Wang; Xudong Wang; Xingye Zhou; Guang Yang; Lei Zhang (Advances in Materials Science and Engineering)
Asphalt suffers from a series of aging processes in the natural environment. This is a significant factor in asphalt pavement diseases. Research of the properties of the decay processes in the natural weathering of asphalt will be helpful in distinguishing the characteristics of the various types of asphalt and in the selection of pavement materials. Neat asphalt A70, a styrene-butadiene-styrene- (SBS-) modified asphalt, and crumb-rubber-modified asphalt AR are exposed to outdoor conditions to weather naturally. This process is traced by testing the basic physical properties and the surface free energy of asphalts, using the sessile drop method. Results illustrate that the basic physical properties of asphalt change significantly during the natural weathering process and that the rubber asphalt has the superior aging resistance, while the neat asphalt A70 has a high aging susceptibility. Furthermore, the presence of the SBS and rubber-powder modifiers transforms the change trend of the surface free energy of neat asphalt. The adhesion work between aggregate and asphalt can be used to quantitatively evaluate the adhesive properties between them. Meanwhile, the presence of moisture between the asphalt and aggregate changes cohesive failure into adhesive failure.